The Relationship of Peer Conformity with Student Discipline in School - Syahrul Fahmi; Dina Sukma (Jurnal Neo Konseling, 2021)
Peer conformity is an action or behavior of a person that is displayed due to the influence of others, namely peers. The aspects of peer friendship are normative and informational. Discipline is a condition that is created and formed through an attitude that shows the values of obedience, obedience, order, and order. Discipline aspects are dress, punctuality, social behavior, and learning ethics. The purpose of this study was to see the relationship between peer conformity and student discipline at SMK N 1 Batipuh. This type of research is descriptive and correlational research using quantitative methods. The research subjects were 84 students who were in class XII at SMK N 1 Batipuh who were registered in the 2020/2021 school year. The research findings reveal that (1) peer friendship is generally in the medium category, (2) student discipline in general is in the sufficiently disciplined category, (3) there is a significant relationship between peer friendship and student discipline in school. So the better the student's peer conformity, the more obedient he or she is in implementing discipline. Based on the findings of this penalty, it is hoped that the counseling teacher or counselor can provide assistance in the form of Guidance and Counseling.